2018
DOI: 10.1039/c7ra11820a
|View full text |Cite
|
Sign up to set email alerts
|

Treatment adherence among sputum smear-positive pulmonary tuberculosis patients in Xinjiang, China: a prospective study

Abstract: Background: Despite great effort to control tuberculosis (TB), low treatment adherence threatens the success of drug therapy, increases the risk of TB transmission, and leads to the development of drug resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…the knowledge, attitude, and practice level of newly treated smear-positive pulmonary tuberculosis patients. Therefore, in the management of newly treated smearpositive pulmonary tuberculosis patients, attention should be paid to communicating with and effectively guiding patients and their families, as well as improving patient compliance to improve the knowledge, attitude, and practice level of newly treated smear-positive pulmonary tuberculosis patients and promote overall rehabilitation [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…the knowledge, attitude, and practice level of newly treated smear-positive pulmonary tuberculosis patients. Therefore, in the management of newly treated smearpositive pulmonary tuberculosis patients, attention should be paid to communicating with and effectively guiding patients and their families, as well as improving patient compliance to improve the knowledge, attitude, and practice level of newly treated smear-positive pulmonary tuberculosis patients and promote overall rehabilitation [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the rate of taking drug was just 48.8% in the villages after internet off at week 6, which may re ect the real treatment compliance rate of village patients by using DOTS as the book marks being always 100% could not re ect the real compliance for taking anti-TB medicine. We believe the low of compliance for taking drugs is the key for the high prevalence of TB in rural area of XUAR, comparing those in Jiangsu (89%), Anhui (90.5%), and Ningxia (93.3%) of China [21] . The developed eDOTS system for promoting compliance may meet the need of control TB in high endemic areas in Xinjiang as the traditional DOTS was not successful in the region.…”
Section: The System Of Edots Is An Effective Tool For Increasing Tb Tmentioning
confidence: 91%
“…Although the international TB control strategy-DOTS was introduced to improve the cure of TB TB control programmes are not fully functioned as required by the guidelines in the remote and impoverished areas of China [19] . Some surveys conducted in recent years have shown that treatment compliance among TB patients is not ideal in China with DOTS management [19][20][21] . In our study, the rate of taking drug was just 48.8% in the villages after internet off at week 6, which may re ect the real treatment compliance rate of village patients by using DOTS as the book marks being always 100% could not re ect the real compliance for taking anti-TB medicine.…”
Section: The System Of Edots Is An Effective Tool For Increasing Tb Tmentioning
confidence: 99%
“…27 The overall pooled estimated prevalence for the Asia region was 17% (95% CI 16% to 18%). The highest pooled prevalence was noted in Southern Asia (22% (95% CI 16% to 29%)), [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] followed by Eastern Asia (18% (95% CI 16% to 20%)), [43][44][45][46][47][48][49][50][51][52][53][54][55] South East Asia (16% (95% 4% to 28%)), [56][57][58][59][60][61] Western Asia (10% (95% 5% to 15%)) [62][63][64] and Central Asia (6% (95% CI 5% to 7%)). 65 66 (figure 2) Subgroup analysis based on the duration of treatment interruption (36 studies, excluded non-defined duration of treatment interruption), demonstrated the pooled prevalence for ≥2 months interruption was 10% (95% CI 9% to 11%), which was much lower than another subgroup that considered the minimum duration of <2 months, 28% (95% CI 20% to 36%) (online supplemental figure S1).…”
Section: Prevalence Of Tb Treatment Interruptionmentioning
confidence: 99%